Early maladaptive schemas in episodic and chronic migraine in adolescents - Güler Aksu, Gülen; Kayar, Ozan; Tufan, Ali Evren; Kütük, Meryem Özlem; Özdağ Acarli, Ayşe Nur; Sucu, Damla Hazal; Taşdelen, Bahar; Toros, Fevziye; Özge, Aynur (Frontiers in Neurology, 2023)
Introduction Psychotherapies, such as schema therapy, are receiving increasing attention in the management of pediatric headaches. The purpose of this study was to investigate early maladaptive schemas (EMSs) in adolescents with episodic migraine (EM) and chronic migraine (CM). Methods This clinic-based, cross-sectional study consisted of 167 adolescents, aged 12–18, who were diagnosed with EM (n = 140) and CM (n = 27). The clinical characteristics of migraine, its accompanying symptoms, EMSs, the interrelationship of EMSs, depression, and anxiety were evaluated. We specifically analyzed psychopathology and abuse history as covariates in this study. Results Defectiveness/shame, mistrust/abuse, abandonment/instability, enmeshment/undeveloped self, self-sacrifice, and subjugation schemas were more prevalent in the CM group. In terms of schema domains, the CM group scored significantly higher in disconnection/rejection and other orientations. Psychopathology did not affect the EMS scores, but a history of sexual abuse did. In patients with EM, a relationship was found between the variables of anxiety, depression, and five of the EMS domains. On the other hand, the CM group showed a significant relationship with anxiety, hypervigilance/inhibition, disconnection/rejection, and other orientation domains. Discussion This study highlights the value of EMSs, anxiety, and depression in young people with EM and CM. Schema therapy and schema-based therapeutic interventions should be researched, especially in pediatric migraine, as they may potentially prevent the progression to treatment-resistant migraine.